Adoption of scientific milking, calf rearing and housing management practices by the buffalo owners - RATHORE, RANJEET SINGH; VERMA, R.K; SINGH, DAYABABD (Indian Journal of Animal Production and Management, 2017)
The present study was carried out in Jhunjhunu district of Rajasthan to find out the adoption level ofscientific management practices. A random sample of 400 buffalo owners were selected from five blocksof the district and adoption percentage of scientific milking, calf rearing and housing management practiceswere studied. It was observed that milking of buffaloes with politely, gently and quickly (87.25%), washingof milking buckets and hands before milking (86.75%), regularity in milking hours (79.00%) and milkingat clean and separate place (78.00%) were more adopted by the respondents in milking managementpractices. The overall adoption of milking management practices was 56.09 percent. Regarding adoptionof scientific calf rearing practices, it was revealed that proper cleaning of mucous from mouth and nostrils(71.63%), colostrum feeding to newly born calves within one to two hours after birth (65.88%) and cuttingand disinfection of naval cord (56.25%) were more adopted by the buffalo owners. The overall adoptionof calf rearing management practices was 38.95 percent. In adoption of housing management practices,it was observed that housing of buffaloes according to climatic conditions (87.00%), adequate floor spacein the buffalo shed (80.63%), proper orientation of buffalo shed (51.00%) and pucca manger with optimumdimension (43.75%) were moderately adopted by the buffalo owners. The overall adoption of housingmanagement practices was 47.14 percent. It was revealed from the study that adoption level of milkingmanagement practices was quite satisfactory in comparison to calf rearing and housing managementpractices.